The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/ajmg.c.31390
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacogenetics implementation: Approaches, successes, and challenges

Abstract: Current challenges exist to widespread clinical implementation of genomic medicine and pharmacogenetics. The University of Florida (UF) Health Personalized Medicine Program (PMP) is a pharmacist-led, multidisciplinary initiative created in 2011 within the UF Clinical Translational Science Institute. Initial efforts focused on pharmacogenetics, with long-term goals to include expansion to disease-risk prediction and disease stratification. Herein we describe the processes for development of the program, the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
177
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(188 citation statements)
references
References 15 publications
1
177
1
Order By: Relevance
“…Approximately 25–35% of individuals of European and African ancestry and ~ 60% of Asians carry at least one copy of no function allele [33]. CYP2C19 *3, *4, *5, *6, *7, and *8 are other less frequent no function alleles, with *3 and *8 being the most common among this group [34]. Poor metabolizers (PM), carrying two copies of CYP2C19 no function alleles make up about 2–5% of European and African individuals and 15% of Asians [35].…”
Section: Cyp2c19 Polymorphisms and Phenotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 25–35% of individuals of European and African ancestry and ~ 60% of Asians carry at least one copy of no function allele [33]. CYP2C19 *3, *4, *5, *6, *7, and *8 are other less frequent no function alleles, with *3 and *8 being the most common among this group [34]. Poor metabolizers (PM), carrying two copies of CYP2C19 no function alleles make up about 2–5% of European and African individuals and 15% of Asians [35].…”
Section: Cyp2c19 Polymorphisms and Phenotypesmentioning
confidence: 99%
“…On the other hand, the identified increased function polymorphism in CYP2C19 (*17: rs12248560) contributes to enhanced clearance of drugs metabolized by CYP2C19. This is also a common polymorphism in CYP2C19 with approximately 30% of individuals of European and African ancestry [34,36] and ~ 2–4% of Asians carrying at least one copy of CYP2C19*17 [37]. Individuals with two copies of the normal function allele are classified as CYP2C19 normal metabolizer status (NM) while individuals with one normal function allele and one increased function allele (*17) are rapid metabolizers (RM).…”
Section: Cyp2c19 Polymorphisms and Phenotypesmentioning
confidence: 99%
“…In the past decade, candidate gene and genomewide association studies (GWAS) have identified specific genetic variants underlying the physiological response to highly prescribed medications, including warfarin [2][3][4][5], clopidogrel [6] and statins [7], to name a few. The appeal of personalized or precision medicine has prompted many clinics to implement genetic testing for these variants [8][9][10][11][12], often despite little [13,14] or even contrary [15] evidence regarding clinical utility. Among the consequences of this recent rise in clinical genotyping and sequencing has been the growing recognition that pharmacogenetic variants regularly display pleiotropic effects [16] incidental to the original purpose of testing [17][18][19].…”
mentioning
confidence: 99%
“…[1] Nonetheless, the translation of pharmacogenomic testing into routine clinical practice has been slow due to several obstacles towards its implementation [2][3][4]. Currently, the routine use of clinical pharmacogenomics is limited to centers with resources to overcome these obstacles [5][6][7][8][9].…”
Section: Background and Significancementioning
confidence: 99%